Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai pada Unit Pelaksana Teknis (UPT) Stadion Jalak Harupat Kabupaten Bandung - R, Rudiana (Madani: Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study is to determine work motivation in the technical implementation unit (UPT), to determine employee performance and to determine work motivation towards performance in the technical implementation unit of the Jalak Harupat stadium, Bandung Regency. With the research method, the author intends to collect data and observe carefully regarding certain aspects related to the problem being studied so that data will be obtained to support the preparation of the research report. In this study, the author uses a descriptive method with a quantitative approach, where the data obtained is expressed in the form of numbers, scores and their analysis using statistics. The results of the research conducted are in general the work motivation of employees at the Technical Implementation Unit (UPT) of the Jalak Harupat Stadium, Bandung Regency. that work motivation is in the very good category, which is 55.02%. This means that employees of the Technical Implementation Unit (UPT) of Jalak Harupat Stadium, Bandung Regency already have quite good motivation and employee performance at the Technical Implementation Unit (UPT) of Jalak Harupat Stadium, Bandung Regency. The results of the study showed that employee performance is in the very good category, which is 59.27%. The work motivation of employees of the Technical Implementation Unit (UPT) of Jalak Harupat Stadium, Bandung Regency has a significant influence on employee performance. This means that if employee work motivation is high, employee performance will also be high. Work motivation affects employee performance by 31.40% and if the agency increases employee work motivation, employee performance will increase by 33.83%.